The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s10633-017-9605-y
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral cancer-associated retinopathy: diagnosis, serology and treatment

Abstract: Although rare, unilateral CAR does occur and in cases with high clinical suspicion an oncological work-up is mandatory. Aggressive cancer treatment combined with steroids and rituximab can lead to normalization of the clinical and ERG phenotype, with clearing of antiretinal antibodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…Despite the fact that anti-TRPM1 autoantibodies have been mostly reported in cases of metastatic melanoma, other groups have also reported patients with carcinoma. Interestingly those also revealed a MAR-like ON-bipolar cell dysfunction on ERG and anti-TRPM1 autoantibodies documented by western blot and immunofluorescence on monkey retina tissue [10,44]. Consequently, as patients with carcinoma can present an ON-bipolar cell dysfunction, a better classification of these two types of paraneoplastic syndromes would be paraneoplastic with photoreceptor defect (usually addressed as CAR) and paraneoplastic with ON-bipolar defect (usually addressed as MAR) [47].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that anti-TRPM1 autoantibodies have been mostly reported in cases of metastatic melanoma, other groups have also reported patients with carcinoma. Interestingly those also revealed a MAR-like ON-bipolar cell dysfunction on ERG and anti-TRPM1 autoantibodies documented by western blot and immunofluorescence on monkey retina tissue [10,44]. Consequently, as patients with carcinoma can present an ON-bipolar cell dysfunction, a better classification of these two types of paraneoplastic syndromes would be paraneoplastic with photoreceptor defect (usually addressed as CAR) and paraneoplastic with ON-bipolar defect (usually addressed as MAR) [47].…”
Section: Introductionmentioning
confidence: 99%
“…However, no skin phenotype has been documented in TRPM1-related cCSNB [21][22][23]. Recently, autoantibodies against TRPM1 were identified in patients with MAR, as well as in a few patients with other neoplasms [10,11,[35][36][37][38][39][40][41][42][43][44][45][46]. Despite the fact that anti-TRPM1 autoantibodies have been mostly reported in cases of metastatic melanoma, other groups have also reported patients with carcinoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors also showed that the subgroup most responsive to immunosuppression treatment was the paraneoplastic AIR group and the least responsive was the npAIR group [13]. A case of unilateral TRPM1-positive CAR associated with adenocarcinoma of the right ovary has been reported [14]. The patient was treated with rituximab, monoclonal antibody, and corticosteroids which resulted in a visual acuity of 20/20, symptomatic improvements, and normalization of the ERGs.…”
Section: Discussionmentioning
confidence: 98%
“…99 Patients present with scotomas, positive visual scintillations (photopsia), and photophobia. The disease is most commonly bilateral but can be asymmetrical, and rarely unilateral 100 Patients with a history of migraine may be mistakenly diagnosed with persistent migraine aura. Initial funduscopic examination may be normal.…”
Section: Autoimmune Retinopathymentioning
confidence: 99%